Fertility, Child Work and Schooling Consequences of Family Planning Programs: Evidence from an Experiment in Rural Bangladesh - Nistha Sinha (Yale University, Economic Growth Center, 2003)
Despite the attractiveness of experiments from the perspective of program evaluation, there have been very few program experiments in the area of family planning. This paper evaluates an ongoing family planning program experiment in rural Bangladesh. The paper estimates the effect of mothers' program exposure on fertility and children's time allocation. The results show that while the program was effective in reducing fertility, it had no significant impact on children's school enrollment. However, the program appears to have significantly raised boys' participation in the labor force.
Keywords: J13; J22; I21; 330; fertility; child labor; school enrollment; program evaluation; Familienplanung; Fertilität; Zeitverwendung; Bildungsverhalten; Ländlicher Raum; Bangladesch